Faktor-Faktor yang Menyebabkan Materi Muatan Undang-Undang Bertentangan Dengan UUD 1945 - Samosir, Daniel (Jurnal Konstitusi, 2015)
In the term of office of the legislators 2004/2009 period, a lot of the Bills which passed into legislation were not in favour of the people. Because of that, those      Bills became prejudice to the society due to the lack of conformation to what the people aspired to in the constitution (UUD 1945) which is the source and basis for the establishment of the legislation. Therefore, many legislation were tested with judicialreview by the constitutional court on the application of the public. Based on this judical review and the usage of normative research by the author, it is found that substances of the legislation are contrary to the constitution (UUD 1945). Because the legislation specified in the list of Prolegnas made by the parlement (DPR) and the President has not fully used clear, precise and consistent criteria. Therefore, the legislation established by parlement 2004/2009 period do not meet the principles of the establishment of the legislation according to the act Number  12 Year  2011 on the establishment of the legislation.